Destination pluto: New horizons performance during the approach phase. (November 2016) - Flanigan, Sarah H.; Rogers, Gabe D.; Guo, Yanping; Kirk, Madeline N.; Weaver, Harold A.; Owen, William M.; Jackman, Coralie D.; Bauman, Jeremy; Pelletier, Frederic; Nelson, Derek; Stanbridge, Dale; Dumont, Phillip J.; et al.
Abstract: The New Horizons spacecraft began its journey to the Pluto-Charon system on January 19, 2006 on-board an Atlas V rocket from Cape Canaveral, Florida. As the first mission in NASA's New Frontiers program, the objective of the New Horizons mission is to perform the first exploration of ice dwarfs in the Kuiper Belt, extending knowledge of the solar system to include the icy "third zone" for the first time. Arriving at the correct time and correct position relative to Pluto on July 14, 2015 depended on the successful execution of a carefully choreographed sequence of events. The Core command sequence, which was developed and optimized over multiple years and included the highest-priority science observations during the closest approach period, was contingent on precise navigation to the Pluto-Charon system and nominal performance of the guidance and control (G&C) subsystem. The flyby and gravity assist of Jupiter on February 28, 2007 was critical in placing New Horizons on the path to Pluto. Once past Jupiter, trajectory correction maneuvers (TCMs) became the sole source of trajectory control since the spacecraft did not encounter any other planetary bodies along its flight path prior to Pluto. During the Pluto approach phase, which formally began on January 15, 2015, optical navigation images were captured primarily with the Long Range Reconnaissance Imager to refine spacecraft and Pluto-Charon system trajectory knowledge, which in turn was used to design TCMs. Orbit determination solutions were also used to update the spacecraft's on-board trajectory knowledge throughout the approach phase. Nominal performance of the G&C subsystem, accurate TCM designs, and high-quality orbit determination solutions resulted in final Pluto-relative B-plane arrival conditions that facilitated a successful first reconnaissance of the Pluto-Charon system.